THE IMPACT OF MARKETING ETHICS ON IMPROVING PERCEIVED SERVICE QUALITY AND MAXIMIZING COMPANY VALUE (AN APPLIED STUDY ON A SAMPLE OF BANKS LISTED ON THE IRAQ STOCK EXCHANGE) - Liqaa Miri Habeeb (Scholar Express Journals, 2022)
The research aims to demonstrate the impact relationship between marketing ethics and each of the perceived quality of service and the value of the company, by determining the role that these ethics can play in maintaining existing customers and gaining new customers in a manner that is commensurate with the developments and changes that accompanied the contemporary business environment that came quickly. And successively, the research was applied in a sample of Iraqi commercial banks listed in the Iraqi stock market during the year 2021. A questionnaire was designed in order to show the effect relationship between the research variables through the use of a set of appropriate statistical methods. Which is consistent with their expectations towards the service provided, as well as maximizing the value of the company from the point of view of both management and customers.
Keywords: commercial; service; value; point